PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN DI PT. X - APRIANTO, CENDY (Jurnal Ilmu Manajemen (JIM), 2016)
This research aims to discuss Work motivation and job satisfaction in an impetus or stimuli that can affect the performance of the employee, the employee’s performance in this regard will be more optimal at in PT. X. The sampling technique using random sampling method. The population this research is all employees PT. X on the human resources governance, quality, and development of the company. Samples that being taken are 86 employees. The instrument of this reseacrh using multiple linear regression analysis with PSAW Statistics 20 software. The results of this research show that the work motivation the significant effect on performance of employees pass trough job satisfaction in PT. X on the human resources governance, quality, and development of the company eitherpartially or simultaneous. Keywords: Work Motivation, Job Satisfaction, Employee Performance